(untitled) (Global Journal of Science Frontier Research, 2011)
In this paper, a combinatory method of the sumudu transform and the homotopy perturbation method is proposed for solving one dimensional non-homogeneous partial differential equations with a variable coefficient. This method presents an accurate methodology to solve nonhomogeneous partial differential equations with a variable coefficient. The obtained approximate solutions are compared with exact solutions and those obtained by other analytical methods, showing reliability of the present method. The comparison shows a precise agreement between the results, and introduces this new method as an applicable one which it needs fewer computations and is much easier and more convenient than others, so it can be widely used in science and engineering.